Defining public goods : an institutional approach to community-building and negotiating inter-community conflict - O'Brien, David J. (Edward Elgar Publishing, 2021)
"Through the lens of an economist's notion of public goods, David J. O'Brien analyzes the dual problems of declining communities and polarizing conflicts between metropolitan and rural communities. This macro-level Institutional approach requires a precise definition of the specific ways in which community-level challenges can negatively affect a larger voting public. The author describes in detail how seemingly intractable community-level problems and inter-community conflicts have been substantially reduced by framing them in terms of the self-interest of a larger polity. Examples include the Federalist papers, written in defense of the US Constitution, New Deal institutions created during the Great Depression, the post-World War II European Union, and more recent macro-level institutional changes that are assisting, in varying degrees, rural community sustainability in the US, Kenya, Rwanda and Russia. O'Brien's extensive community-level research experience in urban and rural communities that covers multiple historical periods, will appeal to inter-disciplinary social scientists, development specialists and persons looking for a hopeful, practical approach to solving the challenges of globalization"--